Tumor Prognostic Prediction of Nasopharyngeal Carcinoma Using CT-Based Radiomics in Non-Chinese Patients - Intarak, Sararas; Chongpison, Yuda; Vimolnoch, Mananchaya; Oonsiri, Sornjarod; Kitpanit, Sarin; Prayongrat, Anussara; Kannarunimit, Danita; Chakkabat, Chakkapong; Sriswasdi, Sira; Lertbutsayanukul, Chawalit; Rakvongthai, Yothin (Frontiers in Oncology, 2022)
Purpose: We aimed to construct predictive models for the overall survival (OS), progression-free survival (PFS), and distant metastasis-free survival (DMFS) for nasopharyngeal carcinoma (NPC) patients by using CT-based radiomics. Materials and methods: We collected data from 197 NPC patients. For each patient, radiomic features were extracted from the CT image acquired at pretreatment via PyRadiomics. Feature selection was performed in two steps. First, features with high inter-observer variability based on multiple tumor delineations were excluded. Then, stratified bootstrappings were performed to identify feature combinations that most frequently achieved the highest (i) area under the receiver operating characteristic curve (AUC) for predicting 3-year OS, PFS and DMFS or (ii) Harrell’s C-index for predicting time to event. Finally, regularized logistic regression and cox proportional hazard models with the most frequently selected feature combinations as input were tuned using cross-validation. Additionally, we examined the robustness of the constructed model to variation in tumor delineation by simulating 100 realizations of radiomic feature values to mimic features extracted from different tumor boundaries. Results: The combined model that used both radiomics and clinical features yielded significantly higher AUC and Harrell’s C-index than models using either feature set alone for all outcomes (p < 0.005). The AUCs and Harrell’s C-indices of the clinical-only and radiomics-only models ranged from 0.758±0.091 to 0.789±0.082 and from 0.747±0.062 to 0.767±0.074, respectively. In comparison, the combined models achieved AUC of 0.801±0.075 to 0.813±0.078 and Harrell’s C-indices of 0.779±0.066 to 0.796±0.069. The results showed that our models were robust to variation in tumor delineation with the coefficient of variation ranging from 4.8% to 6.4% and from 6.7% to 9.3% for AUC and Harrell’s C-index, respectively. Conclusion: Our results demonstrated that using CT-based radiomic features together with clinical features provided superior NPC prognostic prediction than using either clinical or radiomic features alone.